Inefficient rushes in auctions. Issue 1 (1st February 2018) - Hernando‐Veciana, Ángel; Michelucci, Fabio
Abstract : We analyze a setting common in privatizations, public tenders, and takeovers in which the ex post efficient allocation, i.e., the first best, is not implementable. Our first main result is that the open ascending auction is not second best because it is prone to rushes, i.e., all active bidders quitting simultaneously, that undermine its efficiency. Our second main result is that the second best can be implemented with a two‐round auction used in real‐life privatizations. We also show how this result generalizes using a survival auction with a novel tie‐breaking rule.